Natural resources as a value important to the development of ecological consciousness of the polish society - Żeber–Dzikowska Ilona; Chmielewski Jarosław; Lachowski Stanisław (Environmental Protection and Natural Resources, 2016)
The authors examine a very important issue concerning the concept of public consciousness and ecological consciousness of a human. They present ecological consciousness through indicating its level and factors that determine it. They discuss questions connected to shaping ecological consciousness in teachings of Saint John Paul II, sustainable development, eco-philosophy, and pro-ecological attitudes.